2019
DOI: 10.1002/elps.201900168
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of in vitro neural functional connectivity on a neurofluidic device

Abstract: Understanding the mechanism of functional connectivity in neural system is of great benefit to lot of researches and applications. Microfluidics and microelectrode arrays (MEAs) have been frequently utilized for in vitro neural cultures study. However, there are few studies on the functional connectivity of neural cultures grown on a microfluidic chip. It is intriguing to unveil the influences of microfluidic structures on in vitro neuronal networks from the perspective of functional connectivity. Hence, in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…The micrometric dimension of the channels and the controlled flow velocity led to axonal growth and alignment along the channel direction 199 . This latter phenomenon was also reported by Shen and co‐authors who proposed a neuro fluidic micro‐device showing the influence of microfluidic constrain on the functional neural connectivity, which was measured by an integrated MEA inside the microchamber 184 …”
Section: Towards Clinical Translation: Technological Integration With...supporting
confidence: 67%
See 1 more Smart Citation
“…The micrometric dimension of the channels and the controlled flow velocity led to axonal growth and alignment along the channel direction 199 . This latter phenomenon was also reported by Shen and co‐authors who proposed a neuro fluidic micro‐device showing the influence of microfluidic constrain on the functional neural connectivity, which was measured by an integrated MEA inside the microchamber 184 …”
Section: Towards Clinical Translation: Technological Integration With...supporting
confidence: 67%
“…There are some fundamental elements for BoCs design and manufacturing: microchannels, that can be used as neurite growth guide, as scaffolds, or basically to provide perfusion and biochemical gradients; microchambers, to allow spatial separation between different cell types or heterogeneous tissues formation; ECM components for three‐dimensionality representation; electroactive components such as MEAs for stimulation and recording. All those elements are connected to specific functional features as dynamic mechanical stress, mass transport of solutes, analysis of neural electrical activity, and distribution of biochemical cues 183–188 …”
Section: Overview Of In Vivo and In Vitro Epilepsy Models Taking Into...mentioning
confidence: 99%
“…Once a neural circuit is implemented on chip, the possibility to record the electrical activity of the neuronal populations in real time is an essential requirement to acquire a basic understanding of the network functionality. To this aim, several studies have successfully demonstrated the integration of commercial or custom-made multielectrode arrays (MEAs) within microfluidic chips [ 53 , 133 , 134 , 135 , 136 , 137 , 138 ]. In details, MEAs are composed of a set of microelectrodes typically arranged in a matrix configuration, that enable to record extracellular activity of neuronal populations from multiple sites simultaneously in a noninvasive way [ 139 , 140 , 141 ].…”
Section: Biosensors For Measuring Ooc’ Electrical Activitymentioning
confidence: 99%
“…Resting-state functional magnetic resonance imaging (fMRI) has made it possible for researchers to detect alterations in brain functional networks and local spontaneous neuronal activity, which provides new insight into the pathogenesis of neurological diseases (9). At present, there are three reliable technical means widely used in fMRI, including the amplitude of low-frequency fluctuation (ALFF), regional homogeneity (ReHo), and functional connectivity (FC) (10)(11)(12). The ALFF is used to describe spontaneous regional brain activity and ReHo is used to demonstrate the consistency of brain activity (10).…”
Section: Introductionmentioning
confidence: 99%
“…The ALFF is used to describe spontaneous regional brain activity and ReHo is used to demonstrate the consistency of brain activity ( 10 ). FC reveals whether there is connectivity disruption or compensation in the brain regions ( 12 ). In the field of neuroimaging, the known networks for cognitive impairment include the default mode network (DMN), the executive control network (ECN), and the visual network (VN).…”
Section: Introductionmentioning
confidence: 99%